Long transportation duration affects nutrient composition, mycotoxins and microbial community in whole-plant corn silage - Zhang, Caixia; Jiang, Jun; Li, Junfeng; Zhang, Jiming; Zhang, Xinyue; Wang, Hairong (Frontiers in Veterinary Science, 2023)
Introduction Potential nutrient losses and mycotoxin accumulation caused by abnormal fermentation during transportation from cropland to dairy farms leads to the diseases incidence and threatens the health of dairy cows, then further causes financial losses. The aim of this study was to investigate the effects of different transportation times on the nutritional composition, mycotoxins, and microbial communities in whole-plant corn silage (WPCS). Methods Three groups were subjected to different transport times: DY, short (<200 min); ZY, medium time (300–500 min); and CY, long transport time (>600 min). WPCS were collected from the same field, and nutrient composition and microbial composition before and after transportation were analyzed. Results and discussion Our results showed that the temperature of WPCS was higher in the ZY and CY groups than in the DY group (P < 0.01). There were no significant differences in dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), ether extract (EE) and starch contents after different transportation times (P > 0.05), whereas the starch and water-soluble carbohydrates (WSC) contents in the CY group was significantly decreased after transport (P < 0.05). Similarly, the concentration of vomitoxin in the DY and CY groups declined markedly (P < 0.05) and the zearalenone content in the DY group also significantly decreased after transportation (P < 0.05). Regarding the analysis of microorganisms in WPCS, UniFrac-distance matrices and Shannon indices showed differences in the ZY group (P < 0.05), but fungal diversities were not influenced by the transport time (P > 0.05). In the ZY group, the relative abundance of Lactiplantibacillus decreased significantly after transportation (P > 0.05), but the relative abundances of unidentified_Chloroplast, Pantoea, Gluconobacter, unidentified Acetobacter and Acinetobacter increased markedly (P < 0.05). In addition, the relative abundances of Acetobacter and Gluconobacter in the CY group increased after transport (P < 0.05). Among fungal communities, a total of three, nine, and ten different fungal flora were observed in the DY, ZY, and CY groups, respectively, although no difference was found in fungal diversity. In conclusion, increased temperature, loss of starch, and mycotoxin variation were found with increased transport time. This might be the result of competition between bacteria and fungi, and novel technologies will need to be utilized for further exploration of the mechanism.